2020
DOI: 10.1038/s41598-020-67525-1
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning analysis identifies genes differentiating triple negative breast cancers

Abstract: Triple negative breast cancer (TNBC) is one of the most aggressive form of breast cancer (BC) with the highest mortality due to high rate of relapse, resistance, and lack of an effective treatment. Various molecular approaches have been used to target TNBC but with little success. Here, using machine learning algorithms, we analyzed the available BC data from the Cancer Genome Atlas Network (TCGA) and have identified two potential genes, TBC1D9 (TBC1 domain family member 9) and MFGE8 (Milk Fat Globule-EGF Fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…Recent studies have clarified the effect of MFGE8 on cell survival, adhesion, and migration in a wide spectrum of tumor types, such as ovarian cancer ( 36 ) and hepatocellular carcinoma ( 37 ). Consistent with these results, MFGE8 have been found to play a critical role in breast cancer pathobiology and clinical prognosis ( 38 , 39 ). Furthermore, MFGE8 knockdown significantly inhibited both migration and proliferation of tumor cells, attenuating their tumorigenic properties ( 40 ).…”
Section: Discussionsupporting
confidence: 72%
“…Recent studies have clarified the effect of MFGE8 on cell survival, adhesion, and migration in a wide spectrum of tumor types, such as ovarian cancer ( 36 ) and hepatocellular carcinoma ( 37 ). Consistent with these results, MFGE8 have been found to play a critical role in breast cancer pathobiology and clinical prognosis ( 38 , 39 ). Furthermore, MFGE8 knockdown significantly inhibited both migration and proliferation of tumor cells, attenuating their tumorigenic properties ( 40 ).…”
Section: Discussionsupporting
confidence: 72%
“…Our results also suggest that combination treatments aiming at disabling both COX-2 and MFGE8 could represent a therapeutic strategy for the treatment of TNBC. Although MFGE8 has been shown to be overexpressed in TNBC compared with non-TNBC patients [ 45 ], it is also an essential gene for the breast involution process [ 46 ]. Thus, precise examination and attentive care will be required when targeting MFGE8 in clinical settings to avoid any potential side effects related to abnormal mammary gland remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…They reported TBC1D9 as a candidate gene that its expression was linked to improved patient’s survival. Further analysis revealed different roles for TBC1D9 in organelle biogenesis and localization as well as recruitment of NuMA to the mitotic centrosome [ 22 ]. It has been shown that BRCA deficiency causes cortical asymmetry of NuMA-dynein complex in dividing cells which provoke genomic instability and aneuploidy [ 23 ].…”
Section: Discussionmentioning
confidence: 99%